2019
DOI: 10.1061/(asce)mt.1943-5533.0002909
|View full text |Cite
|
Sign up to set email alerts
|

Xanthan Gum Biopolymer as Soil-Stabilization Binder for Road Construction Using Local Soil in Sri Lanka

Abstract: Currently, soil stabilization is used in road construction in Sri Lanka, especially for soft road shoulders. The socioeconomic demand for sustainable development has raised the necessity of new environmentally friendly soil binders for construction engineering practices, including road construction. Industrial residues such as fly and bottom ashes are commonly used to reduce the amount of cement in concrete mixtures or soil stabilization practices, and new biological materials and methods have been introduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(25 citation statements)
references
References 56 publications
1
24
0
Order By: Relevance
“…As previously mentioned, the increase in the mechanical properties over time is related to dehydration of the hydrogels associated with the formation of a soil-xanthan gum matrix, which promotes the aggregation of soil particles [17,34]. Besides the positive effect on the stiffness, compressive and shear strength when using xanthan gum to stabilize soils, the results of direct tensile strength tests [41] and splitting tensile strength tests [40] carried out with air-dried specimens of two sandy soils show an increase in the tensile strength with the increase in the xanthan gum content (from 1.5 to 3%) and with the curing time (up to 30 days).…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously mentioned, the increase in the mechanical properties over time is related to dehydration of the hydrogels associated with the formation of a soil-xanthan gum matrix, which promotes the aggregation of soil particles [17,34]. Besides the positive effect on the stiffness, compressive and shear strength when using xanthan gum to stabilize soils, the results of direct tensile strength tests [41] and splitting tensile strength tests [40] carried out with air-dried specimens of two sandy soils show an increase in the tensile strength with the increase in the xanthan gum content (from 1.5 to 3%) and with the curing time (up to 30 days).…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Several studies have shown that xanthan gum can be used successfully to improve the unconfined compressive strength and stiffness of sands [17,[31][32][33], silty sands [34], clays [17,35], residual soils [36], bentonite, kaolinite [17,25,37], and soft marine clays [24], as well the undrained shear strength of mine tailing material [38]. Additionally, experimental results revealed that the most favourable xanthan gum content for soil stabilization is in the range of 1-1.5% for ambient curing and oven curing [39] and 2.5% for curing in submerged conditions [35].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Biopolymers contain side chains (e.g., trisaccharide) that can interact with charged clay particles, counterions, and pore water through hydrogen bonding (Chenu and GuĂ©rif 1991;). Thus, biopolymers have been reported as effective and ecofriendly soil modification materials owing to their ability to clog pore spaces (Khachatoorian et al 2003;Bouazza et al 2009;Chang et al 2016a;Lee et al 2019;Zhou et al 2020) and enhance interparticle bonding between soil particles (Malik and Letey 1991;Kwon et al 2017;Latifi et al 2017;Chang et al 2020;Soldo et al 2020;Sujatha et al 2020). Moreover, biopolymers have been shown to form viscous hydrogels and interact with the charged surfaces of clays (Chang et al 2015(Chang et al , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Biopolymer content [130][131][132][133] Dehydration time [120][121][122] Moisture content [130] Initial moisture content [131] Fatigue loading [131] Direct Shear Biopolymer content [119,132,133] compaction Biopolymer content [131][132][133] Consistency limits Biopolymer content [131,132,134] Fracture properties Drying and fracture energy [135] Flexible wall permeameter Gas permeability [136] Vane shear test Biopolymer content [134] Consolidation test Biopolymer content [133,137] Sand-clay mixture Unconfined compressive strength Biopolymer content [138,139] Dehydration time [138] Direct Shear shear strength [130] Consistency limits Biopolymer content [138,140] compaction Biopolymer content [138,140] Permeability Hydraulic Conductivity [136,138,139]…”
Section: Biopolymer-clay Interactionmentioning
confidence: 99%